Supplementary information for dissertation "CAR-T cells for Immunotherapy of Cancer" - Sarén, Tina (Uppsala University, 2022)
Supplementary information on the dissertation "CAR T cells for Immunotherapy of Cancer", with the following list of sub-papers:
1. Single-cell RNA analysis reveal subpopulations of CAR T cells correlating with response in lymphoma patients
2. Preclinical evaluation of CAR20(NAP)-T cells for B cell lymphoma
3. Complementary-determining region clustering causes CAR-T cell dysfunction
4. Armed CAR-T cells directed against IL13Rα2 show potent activity against glioblastoma

Differentially expressed genes between responders and non-responders (Fc -1.2 ≤ or ≤ 1.2).

The dataset was originally published in DiVA and moved to SND in 2024.
Supplementary information for dissertation "CAR-T cells for Immunotherapy of Cancer"
Keywords: CANCER; CANCER; Clinical Trials as Topic; Kliniska prövningar som ämne; Glioblastoma; Glioblastom; Medical and Health Sciences; Medicin och hälsovetenskap